2020
DOI: 10.18632/aging.102779
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral small vessel disease is associated with gait disturbance among community-dwelling elderly individuals: the Taizhou imaging study

Abstract: Gait disturbance is considered to be a significant clinical manifestation of cerebral small vessel disease (CSVD). We aimed to investigate the association between different imaging markers of CSVD or total CSVD burden and gait disturbance in a community-dwelling population. In the cross-sectional Taizhou Imaging Study (TIS), 314 participants free of neurological disorders underwent MRI scanning and gait assessment with quantitative wearable devices as well as clinical rating scales. In linear regression, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
1
17
1
1
Order By: Relevance
“…During the walk, data for each stride was extracted by the motion sensor, and turning strides were excluded from analyses. The detailed descriptions of these tests have been reported previously 49 . Based on part of these data, we found that CSVD imaging markers and total CSVD burden are associated with gait disturbance 49 …”
Section: Detailed Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…During the walk, data for each stride was extracted by the motion sensor, and turning strides were excluded from analyses. The detailed descriptions of these tests have been reported previously 49 . Based on part of these data, we found that CSVD imaging markers and total CSVD burden are associated with gait disturbance 49 …”
Section: Detailed Methodssupporting
confidence: 55%
“…Therefore, we assessed participants’ motor function using a set of tests in TIS and designed to follow‐up at 1‐ to 2‐year intervals. Frequently used assessment scales, including the Tinetti test, the Timed‐Up‐and‐Go (TUG) test, and the 3‐meter walking test were performed to assess motor function 49 . In addition, a wearable gait tracking device, composed of an embedded motion sensor and insoles with all sizes (Senno gait, Sennotech Co. Ltd., China), was also used in TIS for the measurement of quantitative gait parameters.…”
Section: Detailed Methodsmentioning
confidence: 99%
“…Participants walked for two trials, and the mean values were used for analysis. We selected the following gait parameters because they sensitively reflect spatio‐temporal gait changes and have shown association or unclear relevance to SVD 6,8,9,11 . Global gait function was indicated by (i) gait speed (cm/s); the pace domain was assessed by (ii) cadence (steps/min) and (iii) stride length (cm); the rhythm domain was determined by (iv) stride time (s) and (v) double‐leg support time (s); the postural control domain was defined as the (vi) walking angle (degree) and (vii) step width (cm); and the variability domain was indicated by (viii) gait speed variability (%).…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral small vessel disease (SVD) is frequently found in individuals with AD, and features seen on neuroimaging usually include white matter hyperintensities (WMH), lacunes, enlarged perivascular spaces (PVS), and cerebral microbleeds (CMB) 7 . These features are not only associated with cognitive impairment but also have been widely considered an important vascular cause of gait disturbance 8–11 . Persons with AD show regional differences in WMH distribution compared with healthy individuals, and regional WMH are differentially associated with specific balance control 10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Smoking and drinking behaviours were classified into two categories, current smokers/drinkers and noncurrent smokers/drinkers, according to information available at the time of the baseline survey. Current smokers were defined as persons who had smoked at least 1 cigarette per day during the preceding year; current drinkers were defined as individuals who consumed 3 or more alcoholic drinks per week for over 6 months [ 26 ]. Household income per month was divided into three levels: low (less than RMB 1000 yuan), moderate (1000-2999 yuan), and high (more than 3000 yuan).…”
Section: Methodsmentioning
confidence: 99%